The Influence of Quality of Work Life and Kaizen Culture on Organizational Commitment Through Job Satisfaction as an Intervening Variable at the Bank of North Sumatra Brigjend Katamso Medan - Khomisah Khomisah; Annio Indah Lestari Nasution; Nuri Aslami (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2023)
The purpose of this study is to identify and analyze organizational commitment to quality of work life, kaizen culture and job satisfaction. In this study, data analysis used a questionnaire designed using the Likert scale method and then calculated using the data processing analysis path. The results of this study are: 1) Quality of work life is proven to have a positive and significant effect on organizational commitment, 2) Kaizen culture is proven to have a positive and significant effect on organizational commitment, 3) Quality of work life is proven to have no negative and not significant effect on satisfaction employee work, 4) Kaizen culture is proven to have a positive and significant effect on employee job satisfaction 5) Job satisfaction is proven to have a negative and insignificant effect on employee commitment to the organization.